High-order harmonic generation spectroscopy by recolliding electron caustics. (5th June 2018) - Faccialà, D; Pabst, S; Bruner, B D; Ciriolo, A G; Devetta, M; Negro, M; Geetha, P Prasannan; Pusala, A; Soifer, H; Dudovich, N; Stagira, S; Vozzi, C
Abstract: Spectral focusing of the recolliding electron in high-order harmonic generation driven by two-color fields is shown to be a powerful tool for isolating and enhancing hidden spectral features of the target under study. In previous works we used this technique for probing multi-electron effects in xenon and we compared our experimental results with time-dependent configuration-interaction singles calculations. We demonstrate here that this technique can be exploited for reconstructing the enhancement factor of the xenon giant dipole resonance and we discuss the sensitivity of this method to macroscopic effects. We then extend the technique to argon in order to test the applicability of this procedure to other targets.